Law like love : queer perspectives on law - Narrain, Arvind. (ed.); Gupta, Alok (ed.) (New Delhi, 2011)
With the landmark Delhi High Court victory in July 2009, sexuality and the law entered mainstream, legal and public discourse in India inviting both celebration and resistance. How do we understand this conversation? The July judgement stands on the shoulders of a much longer history, argue the writers in this contemporary and critical volume on queering the law. A longer history that shapes, unsettles and challenges both legal and queer histories and begins new conversations on the intersections between bodies, politics, activism, sexuality, identity and law. Some playful, some critical and others reflective and irreverent, this unique collection of pieces brings the life, structures and institutions of law alive and shine with relevance in the contemporary moment.
Keywords: Sexuality